(untitled) (International Journal of Statistics in Medical Research, 2014)
Background: Administrative healthcare databases are widely present in Italy. Our aim was to describe the current state of healthcare databases validity in terms of discharge diagnoses (according to the International Classification of Diseases, ICD-9 code) and their output in terms of research. Methods: A systematic search of electronic databases including Medline and Embase (1995-2013) and of local sources was performed. Inclusion criteria were: healthcare databases in any Italian territory routinely and passively collecting data; medical investigations or procedures at patient level data; the use of a validation process. The quality of studies was evaluated using the STARD criteria. Citations of the included studies were explored using Scopus and Google Scholar. Results: The search strategy allowed the identification of 16 studies of which 3 were in Italian. Thirteen studies used regional administrative databases from Lombardia, Piemonte, Lazio, Friuli-Venezia Giulia and Veneto. The ICD-9 codes of the following diseases were successfully validated: amyotrophic lateral sclerosis (3 studies in four different regional administrative databases), stroke (3 studies), gastrointestinal bleeding (1 study), thrombocytopenia (1 study), epilepsy (1 study), infection (1 study), chronic obstructive pulmonary disease (1 study), Guillain-Barre syndrome (1 study), and cancer diseases (4 studies). The quality of reporting was variable among the studies. Only 6 administrative databases produced further research related to the validated ICD-9 codes. Conclusion: Administrative healthcare databases in Italy need an extensive process of validation for multiple diagnostic codes to perform high quality epidemiological and health services research.